The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00384-009-0818-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-6 levels in colorectal cancer patients—a summary of published results

Abstract: Therefore, circulating IL-6 might be prognostic indicator in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
197
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(213 citation statements)
references
References 29 publications
12
197
2
2
Order By: Relevance
“…The serum IL-6 level has been shown to have a prognostic value for hepatocarcinoma patients (Jang et al 2012). In addition, a previous study has demonstrated that an increased serum IL-6 level is associated with an advanced stage of disease and a poor prognosis for colorectal cancer patients (Knupfer and Preiss 2010). Moreover, an increased serum level of IL-6 protein is associated with poor physical performance and muscle strength in older individuals (Cesari et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The serum IL-6 level has been shown to have a prognostic value for hepatocarcinoma patients (Jang et al 2012). In addition, a previous study has demonstrated that an increased serum IL-6 level is associated with an advanced stage of disease and a poor prognosis for colorectal cancer patients (Knupfer and Preiss 2010). Moreover, an increased serum level of IL-6 protein is associated with poor physical performance and muscle strength in older individuals (Cesari et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving the immune status of cancer patients is required for effective cancer immunotherapies. Prospective and retrospective studies have shown that serum IL-6 levels are related to tumor stage and size, metastasis, survival of colon cancer patients [19], chemotherapy efficacy for advanced pancreatic cancer [20], advanced stage and metastasis-related morbidity of breast cancer [21], and the efficacy of personalized peptide vaccination for advanced biliary tract cancer [22]. Results from these studies suggest that IL-6 levels in cancer are not simply useful as promising prognostic biomarkers, but are also related to tumorigenesis and anti-tumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the review by Wouters et al many other markers were shown to be also elevated during COPD exacerbations [18]. The data from the literature show similarly significant changes of the level of markers investigated by us in neoplasm [19] and diabetes [20]. It was also important to include only patients with a similar stage of PAD and to investigate them in a comparable stage of the disease.…”
Section: Discussionmentioning
confidence: 86%